Masticator space abscess following intramuscular stimulation. Issue 11 (15th November 2022) - Kelly, Brendan C; Rosvall, Brandon R; Tabet, Paul; O'Connell, Daniel A
Abstract : A male in his 50s presented to the hospital with preauricular tenderness, trismus and dysphagia. He had intramuscular stimulation of his left temporomandibular joint region performed 4 days prior and described worsening pain and swelling since. A CT scan revealed an abscess involving the left masticator space. Incision and drainage of the abscess was performed, and the patient was discharged home on oral antibiotics 11 days later. This is the first report of masticatory space abscess following intramuscular stimulation of the temporomandibular joint area. Acupuncture and intramuscular stimulation are common complementary medicine therapies that are generally considered safe; however, adverse events such as deep neck space infection have been reported in the literature. Current regulation of training requirements and licensure for needling therapies is highly variable. Standardisation of training and practice guidelines may help mitigate the risk of adverse events related to needling therapies in the future.